Physical literacy for sport injury prevention - building the base for athlete development - Pike, I.; Richmond, S.; Babul, S.; Jacob, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Participation in sport and recreation is a common mechanism for physical activity (PA) among youth. Decades of scientific literature documents participation in sport and PA resulting in positive health outcomes. Despite some literature supporting a relative decline in the number of youth participating in PA generally, studies suggest that over 80% of Canadian youth participate in at least one organized sport, annually. However, the landscape of sport participation in youth in Canada is changing. Increasingly, we note that there are two ends to the sport participation spectrum, one where athletes participate in intense amounts of PA and experience more frequent training, compared to youth at the other end who are less physically active, have low muscular strength and mastery of skills. This dichotomy paints a bleak picture for the physical literacy and overall health in youth, including the athletes that will form the base of athletic programs in the future. Further, and most importantly, literature supports an increase in the risk of sport-related injury at both ends of the spectrum. The objective of this work was to highlight the similarities in physical literacy (PL) and sport injury prevention programming for athlete development, to develop a resource that supports the work of athlete development across sectors, and to discuss opportunities for collaboration for athlete development that includes injury prevention, across the athlete lifespan.